EXCELLENT SERVICE FRONT LINER OFFICER AT THE HOSPITAL, PATJU SHOULD OBEY PATJU WEST LOMBOK REGENCY (ANALYSIS OF INTERPERSONAL COMMUNICATION) - Azmi, Ulul (Politea : Jurnal Politik Islam, 2025)
This study analyzes the quality of excellent service of front liner officers of Patut Patuh Patju Hospital, West Lombok, through an interpersonal communication approach. The background is public complaints about the friendliness, empathy, and responsiveness of officers who are considered weak and lower the image of the hospital. Using a qualitative method with Goffman's dramaturgy theory and interaction openness framework, data was obtained through in-depth interviews, observations, and documentation of six officers and ten selected visitors. Results show that the success of the service is determined by openness, empathy, clarity of message, and the ability to listen actively, but consistency is still low because some officers are less skilled at communicating, using the wrong body language, or slow to respond. The family values of West Lombok shape the expectations of patients, demanding that officers understand the local culture in addition to work procedures. Training, supervision, and motivation have a significant effect on improving the quality of service. This study recommends communication standards based on local wisdom and regular training to strengthen service excellence and satisfaction. These findings are relevant for the human resources policy of regional hospitals in the future. Keywords: Service Excellent, Front Liner, Interpersonal Communication, Compliance Hospital, Quality of Service, Local Culture